Community Empowerment Through Innovation in Mangrove Fruit-Based Dodol (Sonneratia caseolaris) Processing in Resun Village, Lingga Regency: Pemberdayaan Masyarakat Melalui Inovasi Olahan Dodol BerbasisBuah Mangrove (Sonneratia caseolaris) di Desa Resun, KabupatenLingga - prastari, cindytia; Fadli Ilhamdy, Aidil; Manullang, Benny; Viona Selulalae, Anggrei; apriandi, azwin; Jumsurizal, Jumsurizal; rahman, r fathul; Novalina, Sri; Sari Putri, R Marwita; Viruly, Lily; Natasyah, Siti; Wulan, Wulan; Putra, Catur Syahbani (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Resun Village, Lingga Regency, is a coastal area with preserved mangrove forest potential, but the utilization of mangrove fruits such as Sonneratia caseolaris (pedada) is still limited. This activity aims to empower the community through processing pedada fruit into dodol as a local food product with economic and ecological value. The methods used include socialization, dodol making training, organoleptic testing, proximate analysis, and product packaging design. Dodol is made from pedada fruit juice which is boiled and mixed with additional ingredients such as sugar, coconut milk, and glutinous rice flour, then cooked for more than 3 hours. Organoleptic tests by 59 panelists showed the highest level of preference for aroma (2.90) and taste (2.34), while texture received the lowest score (1.68). The results of the proximate test showed that dodol met the quality standards of SNI 01-2986-1992 with a water content of 2.84%, fat 2.84%, protein 2.32%, ash 0.44%, and carbohydrate 68.34%. This activity also succeeded in increasing public awareness of mangrove conservation and forming local business groups based on non-timber forest products.   Keywords: Proximate analysis, Resun Village, Mangrove dodol, Community empowerment, Sonneratia caseolaris, Organoleptic test